Biomedical user adaptive system for smart environments. (1st January 2012) - Krejcar, Ondřej; Janckulik, Dalibor; Motalova, Leona; Czekaj, Petr
Ubiquitous computing (UbiCom) represents an umbrella for Smart Environments, Smart Devices and Smart Interactions. UbiCom also covers an area of user adaptive systems (UAS), which are growing in past time along with expansion of intelligent ubiquitous systems to every piece of embedded device around us. These systems provide many of interesting and useful services to support our day life needs in all areas include biomedical world of our bodies. Every such service needs however to provide their results by some kind of interface. Therefore the need of a simple, intuitive and graphically attractive interface is much appreciated. This paper is focused to several areas of user interface design, user interface adaptivity and visualisation. In all areas of developed system is implemented secured ways.